452 Booting Up the Brain: Intracranial Electroencephalography Reveals Cognitive Network Dynamics During Anesthesia Emergence. (April 2023) - Purger, David Arnold; Eagleman, Sarah; Arikan, Lara; Reid, Brandon; Kaboodvand, Neda; Halpern, Casey H.; Drover, David; Razavi, Babak; Meador, Kimford; Buch, Vivek
Abstract : INTRODUCTION: The dynamic interplay between several large-scale brain networks is thought to underlie human consciousness. The default mode network (DMN) governs internal thought during rest, the central executive network (CEN) drives goal-directed problem solving, and the salience network (SN) detects and integrates new stimuli during the transition between resting and cognitively active states. While scalp electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) have elucidated much about these networks in steady states, intracranial EEG (iEEG) dynamics during state transitions remain largely unclear. METHODS: Seven patients with medically refractory epilepsy underwent robot-assisted stereotactic placement of depth electrodes for epileptic focus localization. Recordings from 422 total iEEG contacts representing 49 distinct cognitive network nodes were obtained during anesthesia emergence. Local-field dynamics and Observer's Assessment of Alertness/Sedation (OAAS) scale state were analyzed in 20s clips for complexity, functional connectivity (FC), and graph communicability metrics. RESULTS: Signal complexity as represented by mean multiscale sample entropy (MSE) of SN and DMN nodes increases significantly during emergence from anesthesia (P < 0.05), driven by a shift from low- to mid-frequency power in key nodes. Intermediate consciousness states demonstrated higher mean MSE and participation coefficient, representing early integrative network behavior, before reaching an optimal balance of segregation and integration at wakefulness. During emergence, between-network FC increased most strongly between SN and CEN nodes. Communicability of SN nodes increased during emergence, driven predominately by increasing communicability of right anterior insula. CONCLUSIONS: Intracranial electroencephalographic recording of brain activity during anesthesia emergence demonstrates a complex but quantifiable interplay of default mode, central executive, and salience network hubs. There may be a greater than previously understood role of right anterior insula in gating transitions in consciousness states.